Moderating Effect of Industry Forces on Entrepreneurial Orientation of Small Hotels Business Performance in Ghana - Adelaide Spio-Kwofie; Eudora Hagan; Sylvia Akua Ansah; Kate Neequaye (Eximia, 2024)
The study examined the moderating effect of industry forces on entrepreneurial orientation to impact on business performance of small-size hotels. A quantitative research approach and a questionnaire survey technique were used to collect the data from 396 small-size hotels. The conceptual model was analyzed through a partial least square using structural equation modelling. It was observed that the direct path relationship of industry forces and business performance was all positive and significant. The study introduced some novelty aspects such as the substitution of construct using industry forces as moderation in the theoretical framework to enhance entrepreneurial orientation to impact on business performance. The study recommends that small hotels strategically position themselves to improve their business performance amid industry forces.